Forage turnip: potential of the species as a soil decompactor, nutrient recycler and biomass producer (Research, Society and Development, 2023)
Cover plants participate in the dynamics that occur in agricultural cultivation areas, mainly by favoring the implantation of subsequent cultures, in addition to helping to structure the soil, in the biological, physical and chemical relationships of the system, helping the formation and maintenance of the soil. balance of the agricultural environment. In this sense, this work aims to describe and evaluate the radish culture as a soil decompacter, nutrient recycler and biomass producer. As a methodology, a narrative review was carried out. The data were obtained from books and articles available in the database of Periódicos Capes and Google Scholar. As main results, it is highlighted that the forage turnip presents itself as a winter cover plant with great capacity for soil decompression and structuring, as well as assisting in the recycling and availability of nutrients to crops, in addition to producing plant biomass for cover and soil protection. The numerous researches related to the subject of cover plants, help in the production of a vast literature, where professionals and producers can make use and raise knowledge for more sustainable practices for agriculture and that harm less the environment. The use of plants as a form of cover is an alternative that contributes to increasing sustainability in agricultural systems, due to the ability to promote soil cover, absorb nutrients from sub-surface layers and release them slowly through the decomposition of soils its waste.